Bolivie, de l'autonomie à l'éclatement ? - Sophie Blanchard (EchoGéo)
On the 4th of may 2008, a referendum was held in the department of Santa Cruz, in eastern Bolivia : the results seem to threaten the country's unity. The ongoing political crisis is a sign of the growing gap dividing Bolivia. The poor Bolivian highlands are Evo Morales's electoral basis - the president, leader of the new Latin-American political leftwing, is an eager defender of the rights of indigenous people -, whereas the wealthier and whiter lowlands are claiming for more autonomy.